Coping strategies among medical and paramedic frontline healthcare workers during the coronavirus pandemic - I. Kammoun; O. Maatouk; R. Kammoun; M. Shiri; H. Nefzi; K. Ben Salah; M. Karoui; F. Ellouz (European Psychiatry, 2022)
Introduction The epidemic of COVID-19 has affected the psychological health of people, especially frontline medical and paramedical staff. Several coping strategies have been used to combat the impact of this virus on their lives.